Pharmacology of Catechins in Ischemia-Reperfusion Injury of the Heart - Kristína Ferenczyová; Lucia Kindernay; Jana Vlkovičová; Barbora Kaločayová; Tomáš Rajtík; Monika Barteková (MDPI AG, 2021)
Catechins represent a group of polyphenols that possesses various beneficial effects in the cardiovascular system, including protective effects in cardiac ischemia-reperfusion (I/R) injury, a major pathophysiology associated with ischemic heart disease, myocardial infarction, as well as with cardioplegic arrest during heart surgery. In particular, catechin, (−)-epicatechin, and epigallocatechin gallate (EGCG) have been reported to prevent cardiac myocytes from I/R-induced cell damage and I/R-associated molecular changes, finally, resulting in improved cell viability, reduced infarct size, and improved recovery of cardiac function after ischemic insult, which has been widely documented in experimental animal studies and cardiac-derived cell lines. Cardioprotective effects of catechins in I/R injury were mediated via multiple molecular mechanisms, including inhibition of apoptosis; activation of cardioprotective pathways, such as PI3K/Akt (RISK) pathway; and inhibition of stress-associated pathways, including JNK/p38-MAPK; preserving mitochondrial function; and/or modulating autophagy. Moreover, regulatory roles of several microRNAs, including miR-145, miR-384-5p, miR-30a, miR-92a, as well as lncRNA MIAT, were documented in effects of catechins in cardiac I/R. On the other hand, the majority of results come from cell-based experiments and healthy small animals, while studies in large animals and studies including comorbidities or co-medications are rare. Human studies are lacking completely. The dosages of compounds also vary in a broad scale, thus, pharmacological aspects of catechins usage in cardiac I/R are inconclusive so far. Therefore, the aim of this focused review is to summarize the most recent knowledge on the effects of catechins in cardiac I/R injury and bring deep insight into the molecular mechanisms involved and dosage-dependency of these effects, as well as to outline potential gaps for translation of catechin-based treatments into clinical practice.